2022
DOI: 10.22302/iccri.jur.pelitaperkebunan.v38i3.534
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Cadmium and its Effect on the Growth of Halfsib Family of Three Cocoa Clones Seedling

Abstract: The issue of cadmium in cocoa beans has become one of the primary considerations in setting quality criteria in chocolate-consuming countries. Using rootstock genotypes that are tolerant to cadmium uptake can provide data on the absorption of cadmium into shoots for recovery. This study examined cocoa plants’ growth and physiological response to cadmium (Cd) accumulation. The research was carried out using polybags in the Greenhouse of the Indonesian Coffee and Cocoa Research Center using a half-sib family of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Few other studies have compared Cd uptake across these specific cultivars. A comparison of Sulawesi 1 and Sulawesi 2 as ungrafted seedlings found that Sulawesi 1 had much higher root uptake of Cd across treatments of 0-8 ppm Cd but that shoot content did not differ between clones (Zakariyya et al, 2022). While root uptake was not measured in the present study, that ranking is consistent only with uptake from the lower-Cd soil (Figure 1A); uptake was highly variable across seedlings grafted onto Sulawesi 1 in the higher-Cd soil (Figure 1B).…”
Section: Cocoa Genetic Effects On CD Uptakementioning
confidence: 99%
“…Few other studies have compared Cd uptake across these specific cultivars. A comparison of Sulawesi 1 and Sulawesi 2 as ungrafted seedlings found that Sulawesi 1 had much higher root uptake of Cd across treatments of 0-8 ppm Cd but that shoot content did not differ between clones (Zakariyya et al, 2022). While root uptake was not measured in the present study, that ranking is consistent only with uptake from the lower-Cd soil (Figure 1A); uptake was highly variable across seedlings grafted onto Sulawesi 1 in the higher-Cd soil (Figure 1B).…”
Section: Cocoa Genetic Effects On CD Uptakementioning
confidence: 99%